Quantitative Assessment of Effectiveness and Utilization of Medical Equipment - Isha Roy Chowdhuri; Arun Kiran Pal (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2022)
The problem of operational efficiency assessment of medical equipment is becoming crucial, due to its increasing requirement in hospitals. It has been observed that a significant amount of medical equipment is out of service for several reasons such as lack of training, maintenance and health technology management. The unexpected failures, downtime associated with breakdown and make ready, loss of production and poor maintenance costs of medical equipment are the major drawback in any hospital. Quality of diagnostic and treatment care provided to patients largely depends on the reliability, availability and maintainability of sophisticated medical equipment. Aim of the present study is to determine quantitatively overall effectiveness and utilization of some medical equipment. Overall Equipment Effectiveness (OEE) and utilization coefficient is the metric measurement of Total Productive Maintenance (TPM) which specifies effective functioning of devices. The results of the effectiveness of the devices are found to be below the standard of 85%. The cause of low effectiveness value was due to poor performance and availability. Equipment utilization is also needed for the evaluation of medical equipment necessity, appropriateness and efficiency of the use in diagnosis and treating a patient. The proposed methodology may be able to increase the amount of working medical equipment by implementing preventive maintenance schedule. The methodology is also validated by failure probability and reliability of the machines.